PERBANDINGAN BENTUK PERTUNJUKAN WAYANG KLlTIK UNDAAN KUDUS DENGAN NGEMPLAK SLEMAN - Suwondo, Suwondo (Institut Seni Indonesia Surakarta, 2011)
Wayang klitik performance atÃ‚Â Sleman, Yogyakarta has some differences and similarities with thatÃ‚Â at Kudus,Ã‚Â Central Java althoughÃ‚Â theyÃ‚Â came fromÃ‚Â the same source. AfterÃ‚Â aÃ‚Â long periodÃ‚Â ofÃ‚Â time,Ã‚Â those who used to be the devoteesÃ‚Â ofÃ‚Â wayang klitikÃ‚Â have lived in different places and the puppeteersÃ‚Â ofÃ‚Â wayang klitik have performedÃ‚Â aÃ‚Â different characteristicÃ‚Â ofÃ‚Â performance.Ã‚Â The story and functionÃ‚Â ofÃ‚Â wayang klitik in Kudus areÃ‚Â more dynamic becauseÃ‚Â wayang klitik is thought not onlyÃ‚Â asÃ‚Â the onlyÃ‚Â entertainment but alsoÃ‚Â as aÃ‚Â ritual for the surroundingÃ‚Â society.Ã‚Â Wayang klitik at Kudus is alwaysÃ‚Â performed annuallyÃ‚Â as aÃ‚Â sendangÃ‚Â (spring) purifying ritual.Ã‚Â Wayang klitik performance at Sleman,Ã‚Â Yogyakarta is held inÃ‚Â the territory with limitedÃ‚Â devotees.Ã‚Â The inhabitantsÃ‚Â ofÃ‚Â the territory comingÃ‚Â from the outside are usually the youngerÃ‚Â generation and educated people who are not familiar withÃ‚Â wayang klitik.Ã‚Â The formÃ‚Â ofÃ‚Â Wayang klitik performance at Sleman, Yogyakarta refers to the normÃ‚Â (pakem)Ã‚Â ofÃ‚Â wayang purwa thatÃ‚Â has beenÃ‚Â traditionally performed in puppetry.Ã‚Â If there isÃ‚Â aÃ‚Â change inÃ‚Â the performance,Ã‚Â it usually hasÃ‚Â something toÃ‚Â doÃ‚Â withÃ‚Â aÃ‚Â puppeteer's own version (sanggit) and theÃ‚Â characteristicÃ‚Â ofÃ‚Â his performance. WayangÃ‚Â klitik performance at Sleman,Ã‚Â Yogyakarta hasÃ‚Â aÃ‚Â tendency to contain aesthetic values and it isÃ‚Â less communicative.Ã‚Â During the last four years,Ã‚Â Wayang klitik at Sleman,Ã‚Â Yogyakarta has beenÃ‚Â performed twiceÃ‚Â onlyÃ‚Â soÃ‚Â that the society tend toÃ‚Â have little interest in it.Ã‚Â The similarityÃ‚Â in the formÃ‚Â ofÃ‚Â the performance between wayang klitik atÃ‚Â Sleman and that at Kudus is that the performance beginsÃ‚Â withÃ‚Â aÃ‚Â major scene (jejer). TheÃ‚Â accompanying melody (gending) for wayang klitik at Sleman is relatively more dynamic and theÃ‚Â garap is more creative and inventive inÃ‚Â nature.Ã‚Â However, the performance has less close relationÃ‚Â with the audienceÃ‚Â soÃ‚Â that thereÃ‚Â isÃ‚Â an impression that the performance is separated from theÃ‚Â audience. On the other hand, wayang klitik performance at Kudus has close relation with theÃ‚Â society. Wayang klitik performance atÃ‚Â Kudus isÃ‚Â more simple and hasÃ‚Â aÃ‚Â religious impression thatÃ‚Â can be appreciated in many waysÃ‚Â ofÃ‚Â communication andÃ‚Â asÃ‚Â may be required by the society. TheÃ‚Â romantic scenes performed at wayang klitik performance at Kudus isÃ‚Â veryÃ‚Â simple in line with theÃ‚Â society's homogenous thinkingÃ‚Â level.Key words:Ã‚Â WayangÃ‚Â Klitik,Ã‚Â function and form, comparison.